SYSTEMATIC LITERATURE REVIEW: DYNAMICS OF INDUSTRIAL RELATIONS IN HYBRID AND REMOTE WORKING SYSTEMS AND THEIR IMPACT ON EMPLOYEE WELFARE - Reza Septian Pradana (RADJA PUBLIKA, 2026)
This study aims to analyze the dynamics of industrial relations in hybrid and remote working systems and their impact on employee well-being through a Systematic Literature Review (SLR) approach. The SLR method is used to systematically identify, evaluate, and synthesize empirical findings based on the PRISMA guidelines. Data sources were obtained from reputable international databases, namely Scopus, ScienceDirect, and PubMed, with a publication period of 2020–2025. Based on the selection process, 30 articles that met the inclusion criteria were analyzed using thematic analysis techniques and synthesized narratively. The results show that hybrid and remote working systems have a dual impact on employee well-being. On the one hand, work flexibility improves work-life balance, job satisfaction, and employee autonomy. On the other hand, there are risks such as social isolation, digital fatigue, and blurring of boundaries between work and personal life that can reduce employee well-being. Furthermore, the transformation of work patterns also influences the dynamics of industrial relations, particularly in aspects of communication, trust, job fairness, and conflict resolution mechanisms. The research findings confirm that industrial relations play a crucial role as a mediating variable in the relationship between flexible work systems and employee well-being. Therefore, the success of hybrid and remote work implementation is determined not only by technological readiness, but also by effective industrial relations management and the balance between work demands and resources. The results of this study provide important implications for developing adaptive, inclusive, and employee-focused work policies in the era of digital transformation.